Disentangling Sex Differences in Use of Reperfusion Therapy in Patients With Acute Ischemic Stroke. Issue 8 (August 2020) - Mainz, Jeppe; Andersen, Grethe; Valentin, Jan Brink; Gude, Martin Faurholdt; Johnsen, Søren Paaske
Abstract : Background and Purpose: Previous studies from local settings have reported that women with acute ischemic stroke have a lower chance of receiving reperfusion therapy treatment, including intravenous thrombolysis and thrombectomy, than men, but the underlying mechanisms of this disparity have not been identified. We aimed to examine sex differences in the utilization of reperfusion therapy focusing on all the phases of pre- and in-hospital time delay in a nationwide population-based cohort. Methods: This study was based on data from nationwide public registries. The study population included patients aged at least 18 years admitted with acute ischemic stroke using emergency medical services in Denmark dispatched after an emergency call in the period 2016 to 2017. Study outcomes included time delays from symptom onset to start of reperfusion therapy and use of reperfusion therapy. Data were analyzed using multivariable quantile regression and logistic regression. Results: A total of 5356 stroke events fulfilled the inclusion criteria. Women (26.6%) were less likely to receive intravenous thrombolysis than men (30.2 %), corresponding to an unadjusted odds ratio of 0.84 (95% CI, 0.74–0.95). In addition, women experienced a 20 minutes longer median time delay from stroke symptom onset to stroke unit arrival than men. Adjusting for onset-to-door time only appeared to have a limited effect on the sex differences in use of intravenous thrombolysis, whereas the odds ratio was 1.06 (95% CI, 0.93–1.21) when adjusting for age at stroke, stroke severity, and cohabitation status. No sex difference was observed for the use of thrombectomy. Conclusions: Women received less reperfusion therapy than men and had a longer time delay from symptom onset to stroke unit arrival, primarily due to a longer delay from symptom onset to emergency medical services call. These differences appeared to be due to the higher age and the higher proportion of women living alone at the time of the stroke. Abstract : Supplemental Digital Content is available in the text.